Empowerment of the Community Through KKN: Raising Awareness of Nutrition and the Risks of Waste for a Sustainable Sedulang Village: Pemberdayaan Masyarakat Melalui KKN: Edukasi Bahaya Sampah dan Kesadaran Gizi Menuju Desa Sedulang Berkelanjutan - Hanggara Arifian; Habibah Nur Rahmawati; Nashwa Azwariyana; Bayu Sandi Fajar; Andi Rangga Purwanto; Rachel Maria Tinambungan; Indra Angelina Seru; Sabilla Fajar Arnetta; Hieskya Anatasya Upa; Haikal Izhar Annazhari; Widodo (B-Creta Publisher, 2026)
Students have a duty to assist the community in addition to their roles as scholars. Community Service Programs (KKN) provide a transformative framework for putting knowledge into practice. Environmental cleanliness and nutritional knowledge were among the village issues that the KKN program addressed in Sedulang Village, Muara Kaman District, Kutai Kartanegara Regency. Outreach on stunting and Dengue Fever (DHF) was part of the work program, as in creating eco-friendly briquettes and environmental education via the